Interventions for infantile haemangiomas of the skin: abridged Cochrane systematic review and GRADE assessments. (19th December 2018) - Novoa, M.; Baselga, E.; Beltran, S.; Giraldo, L.; Shahbaz, A.; Pardo‐Hernandez, H.; Arevalo‐Rodriguez, I.
Summary: Background: Infantile haemangiomas (IH) are soft swellings of the skin that occur in 3–10% of infants. When haemangiomas occur in high‐risk areas or when complications develop, active intervention is necessary. Objective: To update a Cochrane Review assessing the interventions for the management of IH in children. Methods: We searched for randomized controlled trials in CENTRAL, MEDLINE, Embase, LILACS, AMED, PsycINFO, CINAHL and six trials registers up to February 2017. We included 28 trials (1728 participants) assessing 12 interventions. Results: We downgraded evidence from high to moderate/low for issues related to risk of bias and imprecision. Oral propranolol (3 mg kg −1 daily) probably improves clinician‐assessed clearance vs placebo [risk ratio (RR) 16·61, 95% confidence interval (CI) 4·22–65·34; moderate quality of evidence (QoE)]; we found no evidence of a difference in terms of serious adverse events (RR 1·05, 95% CI 0·33–3·39; low QoE). We found the chance of reduction of redness may be improved with topical timolol maleate (0·5% gel applied twice daily) when compared with placebo (RR 8·11, 95% CI 1·09–60·09; low QoE). We found no instances of bradycardia or hypotension for this comparison. Conclusions: Our key results indicate that oral propranolol and topical timolol maleate are more beneficial than placebo in terms of clearance or other measures of resolution, or both, without an increase in harm. Abstract : What's already known about this topic? Infantile haemangiomas become problematic or cause mental distress to children and parents. A first assessment of these interventions in 2011 reported information from four trials with limited evidence. What does this study add? Oral propranolol and topical timolol–maleate are more beneficial than placebo in terms of clearance or other measures of resolution (moderate/low quality of evidence), without an increase in harm (low quality of evidence). The included studies were limited by small sample sizes and risk‐of‐bias issues. Linked Comment: Mellerio. Br J Dermatol 2019; 180 :450–451. Plain language summary available online